Comparison of Robotic and Other Minimally-Invasive Routes of Hysterectomy for Benign Indications. Issue 3 (March 2017) - Swenson, Carolyn W.; Kamdar, Neil S.; Harris, John A.; Uppal, Shitanshu; Campbell, Darrell A.; Morgan, Daniel M.
Abstract : (Abstracted from Am J Obstet Gynecol 2016;215(5):650.e1–650.e8) The popularization of robotic-assisted laparoscopic hysterectomy (RH) over the past decade has provided an alternative approach to performing minimally invasive hysterectomy.